ECO FEMINIST LITERARY ANALYSIS OF CHILDREN’S LITERATURE - Widyaningrum, Agnes; ., Yulistiyanti; Rahayu, Endang Yuliani (Proceeding SENDI_U, 2021)
Reading children’s literature is a good choice for young readers because they have to get involve into reading process to build their habit and if this activity is done continuously, it will be a character. Reading will broaden young reader’s mind to accept all information from reading texts and one example is from reading children’s literature. There are many kinds of children’s literature written in L1 as well as L2 languages because EFL can help young learners adapt to use English in their daily activity. The choice to read English children’s literature will help them learn not just the vocabulary but also the values from the story, such as self-confident, honesty, friendship, bravery, and many more. Those values are some of philosophical values which are the important elements in building students’ character. As a descriptive study in which the purpose is to find out certain phenomena, we chose Randall Van Nostrand’s Helen and The Golden Bee as the object of the study. There are two problems focusing on Helen as the main character in growing her self- confident and helping others though she also experienced some conflicts, internally and externally. This study applied Ecofeminism approach in order to get the findings which show how Helen struggles through her conflicts to build her self-confident and made friends with other creatures, as part of the nature in the environment in which she created on her adventure.